Country-by-Country Reporting: A Step Towards Unitary Taxation? - Miguel Viegas; António Dias (Intereconomics, 2021)
Multinational companies are now obliged to deliver an annual report to the tax authorities with information disaggregated by country (country-by-country reporting) in order to show where the assets and workers are allocated, how profits are distributed and to whom taxes are paid. Unfortunately, these reports are not made public in the European Union, thus preventing public scrutiny about the strategies used by multinational companies to displace profits to tax havens. This article applies the Unitary Taxation regime proposed by the European Commission to US multinational companies. The results confirm a strong bias among the profits distribution towards countries with lower corporate tax rates. Likewise, they confirm the capacity of the Unitary Taxation to promote a fairer distribution of tax revenues. These results can be a good contribution to the current Portuguese presidency of the European Union, which managed to gather important support to move forward with the European public country-by-country reporting directive.
Keywords: 330; Multinationales Unternehmen; Besteuerungsverfahren; EU-Staaten